Axial EBIC oscillations at core/shell GaAs/Fe nanowire contacts. (31st October 2018) - Yang, Mingze; Dvorak, David; Leistner, Karin; Damm, Christine; Watkins, Simon P; Kavanagh, Karen L
Abstract: Electron beam induced current (EBIC) measurements were carried out in situ in the scanning electron microscope on free-standing GaAs/Fe core–shell nanowires (NWs), isolated from the GaAs substrate via a layer of aluminum oxide. The excess current as a function of the electron beam energy, position on the NW, and scan direction were collected, together with energy dispersive x-ray spectroscopy. A model that included the effects of beam energy and Fe thickness predicted an average collection efficiency of 60%. Small spatial oscillations in the EBIC current were observed, that correlated with the average Fe grain size (30 nm). These oscillations likely originated from lateral variations in the interfacial oxide thickness, affecting the resistance, barrier potentials, and density of minority carrier recombination traps.